Eka dharmayuddha : Ahamadābāda ke mila-mazadūroṃ kī laṛāī kā itihāsa - Desai, Mahadev H. (Mahadev Haribhai), 1892-1942 (Navajīvana Prakāśana Mandira, 1941)
History of the textile industry strike in Ahmadābād, India, held during February-March 1918.